Essays on the Constitution - Angelo, AH (Victoria University of Wellington Law Review, 1996)
This article is a book review of Philip A Joseph Essays on the Constitution (Brooker's, Wellington, 1995) pp xxx 411, price $110 (+GST) (hardcover), $57.78 (+GST) (softcover). The book contains 15 essays which cover a unique record of New Zealand's constitutional and political life. Angelo argues that most of the essays are provocative, present new views, and suggest areas for reform. Angelo does lament the lack of pre-Treaty New Zealand constitutional law, and also notes that some of the essays are purely descriptive in nature. Nonetheless, Angelo concludes that the book is compendious and essential reading for those with a special interest in New Zealand political life – constitutional lawyers, political scientists, politicians and public servants alike.